2015
DOI: 10.3917/rpve.532.0113
|View full text |Cite
|
Sign up to set email alerts
|

Des chiffres de la politique à la politique du chiffre : le cas des réformes du financement de la recherche dans les universités belges francophones

Abstract: Distribution électronique Cairn.info pour De Boeck Supérieur. © De Boeck Supérieur. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Secondly, because some of the organizational observations made here have been shared at the scale of six European universities involved in the original EU FP7 project "Gendering the Academy and Research: Combating Career Instabilities and Asymmetries" 1 . Moreover, most of the statements made here -especially the identification of the three logics of action -corroborate those made in the Belgian Walloon Region [9], in France [10], in the Netherlands [11], and other quoted colleagues in other European countries.…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…Secondly, because some of the organizational observations made here have been shared at the scale of six European universities involved in the original EU FP7 project "Gendering the Academy and Research: Combating Career Instabilities and Asymmetries" 1 . Moreover, most of the statements made here -especially the identification of the three logics of action -corroborate those made in the Belgian Walloon Region [9], in France [10], in the Netherlands [11], and other quoted colleagues in other European countries.…”
Section: Introductionsupporting
confidence: 85%
“…Some authors consider that the pursuit of Excellence by universities is based on exclusion mechanisms, and compromises the personal welfare of academics [32]. Belgian scholars have demonstrated that allocating funding on the basis of scientific Excellence criteria contributes to reducing the investment in teaching [9]. In view of these developments, our paper delves into a second sub question: how are the practices of Belgian academics shaping -and being shaped by -Excellence?…”
Section: The Academic Contextmentioning
confidence: 95%
See 2 more Smart Citations